Intensity and Duration of Anticoagulation Therapy in Antiphospholipid Syndrome - Les, Iñigo; Ruiz-Irastorza, Guillermo; Khamashta, Munther A. (Seminars in Thrombosis and Hemostasis, 2012)
Antithrombotic drugs are the therapeutic cornerstone for patients with antiphospholipid syndrome (APS) and thrombosis. Choosing the specific agent (vitamin K antagonists or antiplatelet drugs), the intensity of anticoagulation (e.g., international normalized ratio [INR] range 2.0 to 3.0 or 3.0 to 4.0), and the duration of treatment has been a recurrent matter of debate. A recent consensus document recommends warfarin to an INR range of 2.0 to 3.0 for patients with a first venous thromboembolic event. Higher anticoagulation intensity is recommended for patients presenting with arterial events. Combined therapy with warfarin and aspirin is another possibility, but some authors recommend standard intensity warfarin or aspirin, either as monotherapy. In general, a more intense regimen is warranted for high-risk patients. On the basis of an increased risk of recurrence during the first 6 months following warfarin withdrawal, long-term anticoagulation is considered the standard treatment. Nevertheless, anticoagulation regimes of shorter duration could be given in selected patients with venous thromboembolism who have transient risk factors and a low-risk profile.
Keywords: antiphospholipid syndrome; anticoagulation therapy; intensity; duration